The role of pharmacist in reducing the impact of air pollution on human health - Javorac, Dragana; Marić, Djurdjica; Baralić, Katarina; Antonijević Miljaković, Evica; Buha Djordjević, Aleksandra; Djukić-Ćosić, Danijela; Ćurčić, Marijana; Antonijević, Biljana; Bulat, Zorica (Archives of Pharmacy, 2022)
Polluted air is significant factor with a negative impact on human health. Solving the problem of polluted air requires involvement of the health system and health workers, among whom pharmacists in public pharmacies can stand out as the most accessible health workers with the highest knowledge in the field of toxicology. Considering the indisputable role of pharmacists in improving health and disease prevention, raising public awareness of air pollution health impact and advising patients on activities in case of air pollution, pharmacists would contribute to maintaining health, reducing the burden on the health system and its efficiency and sustainability. The pharmaceutical profession can make a significant contribution to combating the impact of air pollution on human health by increasing the availability of guidelines in the case of polluted air, increasing the availability of air quality monitoring tools, strengthening educational capacity models, participating in regulatory frameworks and improving funding for pharmaceutical services. In order for these responsibilities to be fully incorporated into pharmaceutical practice, it is necessary to: implement education in the field of toxicology, both at basic and higher levels of study in order to develop the necessary competencies; increase public awareness of the health consequences of air pollution, as well as the new roles of pharmacists; develop appropriate guidelines, regulatory and financial support as well as screening tools. With this in mind, the role of pharmacists in reducing the impact of air pollution on human health should be recognized and developed in order to protect human health.